(untitled) (Acta Scientiarum. Agronomy, 2019)
Plants are often exposed to abiotic stresses such as salinity, which represents a barrier to the cultivation of agricultural species mainly in arid and semi-arid regions. This study evaluated the development of four saccharine sorghum genotypes for tolerance to different salinity levels under greenhouse conditions. The experimental design was a randomized complete block arranged in a 5 Ã— 4 factorial scheme, which corresponded to five levels of irrigation water salinity [electrical conductivities of 0.5 (control), 2.5, 5.0, 7.5, and 10.0 dS m-1] and four saccharine sorghum genotypes (CSF 11, CSF 15, P 76 and P 298), with five replicates. The plants were evaluated for dry mass production, leaf area, height, stalk diameter, leaf gas exchange and relative chlorophyll content. The growth and leaf gas exchange measurements of the saccharine sorghum plants were significantly affected by salinity stress. Among the genotypes, CSF 11 and CSF 15 exhibited smaller reductions in growth, whereas P 298 showed the greatest reduction. These findings show that genotype CSF 11 can be classified as the most tolerant to salt stress, and genotype P 298 is the most sensitive.